ANALISIS PENGARUH BELANJA MODAL DAN DANA ALOKASI UMUM TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN LOMBOK TENGAH - Aminy, Muhammad Habibullah; Muhamad Sayuti; Ahmad Ridho Hidayat (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This research is entitled "Analysis of the Influence of Capital Expenditures and General Allocation Funds on Economic Growth in Central Lombok Regency." In this research the researcher wants to see the influence of capital expenditures and general allocation funds on the economic growth of Central Lombok Regency. This type of research is associative quantitative research. Associative research is research that tries to find the relationship between one variable and another variable. The analytical tool used in this research is multiple linear regression analysis. That partially and simultaneously the variable capital expenditure and general allocation funds have a positive effect on the economic growth of Central Lombok Regency is proven by the t-count value of 3.401 and 2.72 > t table 2,229 and the f-count value of 5.362 > f-table 4, 45. The most dominant independent variable fact among the independent variables on economic development is the general allocation fund variable of 2.109. The results of the R-square test for the independent variable on the dependent variable were 0.754 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this research has the meaning that the influence of the independent variable is 0.754 units or 75.4%, this figure is able to explain the dependent variable, while the rest is influenced by other variables not included in this research at 24.6